Risk management in practice: A multiple case study analysis in Italian municipalities - Monia Castellini; Vincenzo Riso (Journal of Risk and Financial Management, 2023)
This paper aims to analyse the ways in which risk management has been embedded in management control systems in Italian municipalities. Through a qualitative method, this study presents multiple case studies from six municipalities with two levels of analysis: content analysis on the information published on the institutional website, and interviews through a questionnaire with open and closed questions addressed to the public managers of the Italian municipalities selected. Moreover, the municipality respondents were classified into medium (two municipalities with over 50,000 inhabitants), medium-high (two municipalities with between 100,000 and 500,000 inhabitants), and high (one municipality with over 500,000 inhabitants). The multiple case studies reported show how there is not a strong level of integration between risk management and the management control system in use. This research is useful to sustain the debate about risk management in the public sector. It should help practitioners and scholars to cover their municipalities' needs.
Keywords: 650; risk management; municipality; practice